PERANAN LEMBAGA TARI TRADISI DALAM MEMPERTAHANKAN TARI TRADISI - Y. Murdiyati - (FBS UNY, 2006)
This article aims at analyzing the role of informal tradition danceorganizations that preserve tradition dances and describing their strategies tomaintain the preservation. The organizations that become the objects are“Irama Tjitra Yogyakarta” in Yogyakarta, “Sekar Budaya Nusantara” inJakarta, and “Tunas Budaya” in Gunungkidul, Yogyakarta Special Territory.The study shows that each organization has a different role and strategies to dothe preservation, among which are regeneration, transformation, transmissionand revitalization.Key words: organization, tradition dance and role